‘Those Boys Are Representing Mashonaland’: Digital Football Fandom, Ethnicity and National Identity Politics in Zimbabwe - Lyton Ncube; Jasper Maposa (Palgrave Macmillan, Cham, 2022)
Football is a crucial site of representation where nations and national identities are [re]imagined. Likewise, whenever the Warriors-Zimbabwe’s senior men national football team play, contestations over national identity often run under the surface. Readily-combustible virtual online platforms become carnivals where such discourses easily find their way. However, academic studies on mundane practices of nationalism such as football fandom in Zimbabwe are few and far between. This chapter explores the convergence of ethnicity, national identity and everyday nationalism discourses in Zimbabwe’s digital football fandom. In essence, the study examines how some Zimbabweans perceive and relate to Zimbabwe’s flagship national football team, nation and national identity at large. Focus is on purposively selected online comments and debates on Facebook fan pages- Dembare Dotcoms and Highlanders FC page during the Warriors’ poor performance at the 2017 Africa Cup of Nations (AFCON) held in Gabon. Findings show that matches involving the Warriors are ritualised ethnic identity wars, always throwing up ontological, philosophical and metaphysical questions on ‘Who is a Zimbabwean? and What is Zimbabwe anyway?’ Wittingly or not, the Warriors are viewed through the polarising ‘Shona’/’Ndebele’, ethnic lens. Following the Warriors’ humiliation in Gabon, most of the comments presumably from the Ndebele speaking Zimbabweans expressed ‘disassociation’ from the ‘embarrassment’, arguing that the team was not representing the ‘nation’ but Mashonaland provinces, as reflected by its composition.